Can serum biomarkers be used to rule out significant intracranial pathology in emergency department patients with mild traumatic brain injury? A Systemic Review & Meta-Analysis. Issue 2 (February 2022) - Rogan, Alice; O'Sullivan, Morgane Brunton; Holley, Ana; McQuade, David; Larsen, Peter
Highlights: The overall quality of evidence regarding diagnostic accuracy of single biomarkers as rule out tests for significant intracranial injury in ED patients with TBI is low. This is largely due to significant clinical variation in included studies that use different populations and CT decision thresholds. Based on current evidence S100B is the only single biomarker with a validated clinical platform, pre-determined cut off threshold and moderate quality evidence. Further research is required before GFAP and UCH-L1 can be used clinically in ED and a validated clinical platform requires development. More robust clinical outcome and economic impact data is required to support biomarker incorporation into clinical decision tools in wider international EDs. Abstract: Background: Interest has mounted into the use of objective clinical biomarkers for traumatic brain injury (TBI). This systematic review and meta-analysis aimed to synthesise the existing evidence investigating the use of serum & plasma biomarkers to exclude significant intracranial injuries seen on CT head scans in patients that present to ED with TBI. Methods: The primary outcome was to review the diagnostic accuracy (sensitivity & specificity) of S100B, GFAP and UCH-L1 to exclude significant intracranial pathology on CT head scan in adults presenting with TBI. Secondary outcomes investigated biomarker performance at different time points, in isolated TBI and multi-trauma and with pre-specified cut offs. Systematic searches were conducted on MEDLINE ® (via PubMed), Cochrane electronic databases and EMBASE from 1 st January 2000 until June 2020. Bias was assessed using QUADAS 2 tool. A narrative synthesis and meta-analysis were performed. PROSPERO registration number CRD42020212206. Results: After screening, 22 papers were included. The total number of patients with TBI was 9, 416. There was significant variation regarding study design, population selection and the clinical threshold/decision rule for CT head request. The diagnostic accuracy of S100B as measured by the range of individual sensitivities and specificities were 63-100% and 5-58%, respectively. Individual sensitivities and specificities for GFAP were 67-100% and 0-89% and for UCH-L1 were 61-100% and 21-63.7% respectively. When measured within 3 hours individual sensitivities & specificities for S100B were 98-100% & 20-58% respectively. The quality of evidence for the primary outcome overall was low. The quality of evidence was low for all secondary outcomes apart from studies that used a pre-specified cut off for S100B which had a moderate strength of evidence. Conclusion: The overall quality of evidence regarding the diagnostic accuracy of single biomarkers as a rule out for significant intracranial injury seen on CT head scans in ED patients with TBI is low. Based on current evidence, S100B is the only single biomarker with a validated clinical platform, pre-determined cut off threshold and moderate quality evidence; at this stage making it the biomarker of choice. More robust clinical outcome and economic impact data is required to support its incorporation into clinical decision tools.